Changing Values on Water in Delta Cities: The case of Guangzhou in China’s Pearl River Delta - Tai, Yuting (A+BE | Architecture and the Built Environment, 2018)
Delta cities worldwide are confronted with great challenges concerning flood risks, environmental pressures and other water-related urban issues. The complexity in both physical and social dimensions lies in diverse (and in many cases conflicting) values held by a wide variety of actors in spatial development. These values are shaped by the long-term impacts of natural forces, political powers, development ideologies, economic models, social structures, and local cultures. Defining the central role of “water” in structuring delta cities, this research applies the value concept as a particular lens to study how water is valued in each society through history. It argues that the recognition of diverse water values can help bridge the interplay between physical and societal systems within the delta, which can play a central role in developing urban planning and design strategies towards sustainable and liveable urban water environments. The thesis develops an empirically tested analytical framework which links value theory with planning and design practices to investigate context-specific spatial transformations as a result of individual and collective value judgements. Four key aspects of water values including flood safety, as well as economic, social and environmental values, are studied, and their interrelationships are discussed. Morphological analyses and value assessments are conducted to explore in what sense spatial changes can be considered an expression of the changing values and what we can learn from it to deal with complex spatial situations. The empirical studies are based on the long-term spatial development of Guangzhou as representative of a historical and rapidly growing delta city in China. Three development stages are illustrated to show different patterns of water-city interactions, the waterways city (before the 1920s) that was mainly structured by natural forces including natural waterways, the functional city (1920s-1970s) that was managed in a highly centralised approach such as functional zoning and large-scale flood defence, and the pluralistic city (after the 1970s) with the tendency towards accommodating plural values of water such as environmental sustainability, social equity and cultural identity. Based on value theory and the empirical studies of Guangzhou, three main characteristics of value transitions can be suggested. First, values change through time in response to the changing conditions of natural dynamics, societal needs, and emerging risks. It is important to recognise the process of transition and its underlying forces to enable a comprehensive understanding of the mechanisms that influence the spatial development and policy-making. Second, value conflicts act as a motivating force for changes in both spatial and social dimensions. Understanding the interrelations between values, either synergic or conflicting, is important to evaluate spatial policies and define future development orientations. Third, the persistence of traditional values within a society over time indicates the core cultures and common interests intrinsic to each society with an adaptive capacity to cope with changing contexts.